Integration of Blockchain Technology in Village Fund Management Based on Sharia Economics - Khairanis, Retisfa; Aldi, Muhammad (Malacca: Journal of Management and Business Development, 2025)
This research aims to analyze the potential integration of blockchain technology in the management of village funds based on sharia economy to improve transparency, accountability, and compliance with sharia principles. The main issues raised are the lack of transparency in the allocation of village funds and the challenges of applying sharia principles in village financial management. The research method uses a qualitative approach with literature studies on the concepts of sharia economy, blockchain technology, and village fund management, as well as case analysis in two pilot villages that have implemented digital financial systems. The results show that blockchain is able to create a decentralized, immutable, and auditable transaction recording system in real time so that it meets sharia principles such as justice ('adl), transparency (openness), and the prohibition of usury. The discussion revealed that blockchain integration can reduce the risk of misuse of funds, facilitate community participation in monitoring, and strengthen trust in village institutions. However, the main challenges lie in the readiness of technological infrastructure, community digital literacy, and regulatory harmonization. The conclusion of the study states that blockchain integration in sharia-based village fund management is feasible to be implemented gradually with the support of training and collaboration between stakeholders. This research provides a practical contribution in the development of an innovative and sharia-compliant village fund management model.